The hermeneutical proposal as criticism and as a criterion for the problem of method - Ángel Pérez, Darío Alberto; Herrera, José Darío (Estudios de Filosofía, 2011)
This article presents a follow-up of the hermeneutic tradition as a criticism proposal as well as a critique proposal to understand the Social Sciences and their methodological possibilities, a follow-up of the researcher’s role in the construction of his objects of study, and the dynamics of History as a phenomenon that requires to be approached with comprehension and not by means of explanation.